2015
DOI: 10.1039/c5cc04528b
|View full text |Cite
|
Sign up to set email alerts
|

A high-efficiency γ-MnO2-like catalyst in toluene combustion

Abstract: A novel γ-MnO2 catalyst obtained by selective removal and other traditional MnO2 catalysts (α-, β-, δ-MnO2) were studied for their catalytic performance in toluene combustion. The new γ-MnO2 catalyst showed the best catalytic activity owing to its three-dimensional macroporous and mesoporous morphology and the γ-MnO2-like structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(91 citation statements)
references
References 24 publications
1
90
0
Order By: Relevance
“…In Figure 2B, O 1s has signals at BE values of 529.9 and 531.6 eV, which correspond to surface lattice oxygen (O latt ) and surface adsorbed oxygen (O ads ), respectively. 51,52 The dominant source of O ads is originate from the As(III) and As(V), which exists as H 3 AsO 3 and H 2 AsO 4 − under the experiment condition (pH 6). And the O latt is belonging to the ZCNs itself, and it will remains invariant during the adsorption process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In Figure 2B, O 1s has signals at BE values of 529.9 and 531.6 eV, which correspond to surface lattice oxygen (O latt ) and surface adsorbed oxygen (O ads ), respectively. 51,52 The dominant source of O ads is originate from the As(III) and As(V), which exists as H 3 AsO 3 and H 2 AsO 4 − under the experiment condition (pH 6). And the O latt is belonging to the ZCNs itself, and it will remains invariant during the adsorption process.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As shown in Figure 5, two peaks centered at 300 and 550 8Cc ould be observed for Mn-MIL-100, and the reduction processt ook place in two steps. The reduction peaks at 300 and 550 8Cw ere attributed to the reductiono fM n 4 + to Mn 3 + and reduction of Mn 3 + to Mn 2 + , [29,30] respectively.O ni ncreasing the calcination temperature to 250 8C, both reduction peaks shifted to lower temperature. Moreover,t he reducibility of amorphous materials followed the trend a-Mn-250 > a-Mn-200 > Mn-MIL-100, which indicated that a-Mn-250 catalysth as stronger low-temperature reducibility and higher mobility of oxygen specieso r oxygen vacancies.…”
Section: Characterizationo Fa Morphouscatalystsmentioning
confidence: 98%
“…In a same way, various structures of MnO 2 i.e., α-, β-, δ-MnO 2 were prepared and their catalytic performances in toluene oxidation were assessed to those of a γ-like MnO 2 obtained by the selective removal of La 3+ from an acid-treated three-dimensional macroporous and mesoporous LaMnO 3 [33]. The best performance of this γ-like MnO 2 over the other MnO 2 polymorphs was ascribed both to the open three-dimensional macroporous and mesoporous morphology leading to higher BET surface areas than conventional syntheses, enhanced surface adsorbed oxygen (O ads ) to lattice oxygen (O latt ) molar ratio (O ads /O latt ) and easier reducibility.…”
Section: Mno X In Catalytic Oxidation Of Toluenementioning
confidence: 99%
“…The common oxidation catalytic reactions generally involved three types of mechanism [35]: Langmuir-Hinshelwood, Eley-Rideal and Mars-Van Krevelen (MkV) mechanism [33]. It is well known that MnO x exhibit strong oxygen storage/release ability due to the fact that they easily undergo a rapid reduction-oxidation cycle through the interaction with reducing or oxidant agents accompany by the formation of manganese ions in various oxidation states.…”
Section: Mno X In Catalytic Oxidation Of Toluenementioning
confidence: 99%